2016
DOI: 10.3389/fmicb.2016.01723
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Dihydropteroate Synthase Genes in Stenotrophomonas maltophilia by LAMP: Implications for Infection Control and Initial Therapy

Abstract: Stenotrophomonas maltophilia is a common nosocomial pathogen that causes high morbidity and mortality. Because of its inherent extended antibiotic resistance, therapeutic options for S. maltophilia are limited, and sulfamethoxazole/trimethoprim (SXT) is the only first-line antimicrobial recommended. However, with the spread of dihydropteroate synthase (sul1 and sul2) genes, global emergence of SXT resistance has been reported. There is an urgent need to develop a rapid and sensitive but cost-efficient method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The identification of bacterial species was performed using a Vitek II bacterial identification system (bioMérieux, Marcy-l'Étoile, France) and further confirmed via a species-specific polymerase chain reaction. 9,14,15 The detection of the sul genes (including sul1 and sul2 genes) was presented as follows: SUL1-F(GCTATTGGTCTCGGTGTCGC) and SUL1-B(GCATGATCTAACCCTCGGTCT) for sul1; SUL2-F(TTTCGGCATCGTCAACATAA) and SUL2-B(CCACGCGACAAGGCATA) for sul2. The PCR reaction volume system and cycling parameters were the same as in our previously published literature.…”
Section: Bacterial Strains and Susceptibility Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of bacterial species was performed using a Vitek II bacterial identification system (bioMérieux, Marcy-l'Étoile, France) and further confirmed via a species-specific polymerase chain reaction. 9,14,15 The detection of the sul genes (including sul1 and sul2 genes) was presented as follows: SUL1-F(GCTATTGGTCTCGGTGTCGC) and SUL1-B(GCATGATCTAACCCTCGGTCT) for sul1; SUL2-F(TTTCGGCATCGTCAACATAA) and SUL2-B(CCACGCGACAAGGCATA) for sul2. The PCR reaction volume system and cycling parameters were the same as in our previously published literature.…”
Section: Bacterial Strains and Susceptibility Testingmentioning
confidence: 99%
“…7,8 Our previous epidemiological survey confirmed that the presence of sul genes was the predominant resistance mechanism for SXT in clinically-isolated S. maltophilia in China. 9 S. maltophilia shows high susceptibility to tetracycline derivatives, including minocycline, doxycycline, and tigecycline, and these antimicrobials can be used as alternatives for the treatment of S. maltophilia infection, even for SXT-resistant strains. 1,2,9 However, an in vitro study by Wei et al found that tetracycline derivatives exhibited bacteriostatic activity against S. maltophilia, which can only inhibit the proliferation of S. maltophilia instead of effectively killing the organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of S. maltophilia infections is limited due to the extensive resistance displayed to most clinically used antimicrobials, and sulfamethoxazole/trimethoprim (SXT) is the only recommended first-line antimicrobial. However, its use is limited by a high incidence of allergic reactions, intolerance, and increasing resistance mediated by the spread of sul1 and sul2 genes ( Toleman et al, 2007 ; Hu et al, 2011 ; Chang et al, 2015 ; Zhao et al, 2016 ). Tigecycline has been reported to retain good in vitro activity against S. maltophilia in worldwide surveillance and multicenter studies, and Wei et al (2016) reported that 80.4% of clinical isolates in China, and 72.7% of SXT-resistant isolates were susceptible to tigecycline, making it a promising alternative antimicrobial for infection treatment ( Stein and Babinchak, 2013 ; Rizek et al, 2015 ; Wei et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…S. maltophilia is emerging as an important multidrug-resistant nosocomial pathogen, being amongst the top three most common non-fermentative Gram-negative bacilli identified in hospitalized patients (5, 33). Despite S. maltophilia being well-adapted to many environments, most infections occur in immunocompromised individuals in the nosocomial setting (10), although community-acquired infections are also on the rise (1).…”
Section: Discussionmentioning
confidence: 99%